Efficacy and safety of prolonged-release hyaluronic acid derivative vaginal application in the postpartum period: a prospective randomised clinical trial. (1st January 2021) - Gustavino, Claudio; Sala, Paolo; Cusini, Nadia; Gravina, Brunella; Ronzini, Cecilia; Marcolin, Diletta; Vellone, Valerio Gaetano; Paudice, Michele; Nappi, Rossella; Costantini, Sergio; Ferrero, Simone; Barra, Fabio
Abstract: Introduction: In puerperium, the hypoestrogenic state induced by delivery and subsequently sustained by lactation may lead to vaginal dryness, burning, and itching sensation, contributing to the onset of sexual dysfunction. Material and methods: This was a prospective, randomized, controlled, open-label study (NCT04560283) for evaluating the effects of application of a prolonged-release hyaluronic acid derivative vaginal gel in restoring sexual function during the postpartum period. Eighty-five patients were randomized to apply prolonged-release Hydeal-D 0.2% vaginal gel (Fidia Farmaceutici, Abano Terme, Italy; n = 43) every three days for 12 consecutive weeks or expectant management ( n = 42). Results: Women undergoing treatment had a more elevate increase in Female Sexual Function Index (FSFI) total score (+15.1 ± 11.9 vs +6.5 ± 8.9, p < 0.001) and a higher decrease in vaginal pH (−1.2 ± 0.7 vs −0.2 ± 1.1; p < 0.001). Moreover, the proportion of vaginal smears with maturation index (VMI) >65 was significantly higher in patients treated (80.6% vs 35.3%; p = 0.004). Edinburgh Postnatal Depression Scale (EPDS) decreased significantly in both groups with no inter-group difference ( p = 0.459). Only two cases (4.8%) of moderate vaginal burning sensation were reported in patients undergoing local vaginal therapy. Conclusions: The results of our study demonstrated that hyaluronic acid derivative vaginal gel (Hydeal-D) was able to improve sexual function of puerperal women in the short-term treatment. KEY MESSAGE: In the puerperium, the hypoestrogenic state induced by delivery and subsequently sustained by lactation may lead to vaginal dryness, burning, and itching sensation, contributing to the onset of sexual dysfunction. Hydeal-D is a prolonged-release hyaluronic acid derivative characterised by elevated resistance to enzymatic breakdown. During puerperium, its local application may improve the vaginal microenvironment by ensuring a better migration and proliferation of cells involved in local tissue repair. Among puerperal women, Hydeal-D vaginal gel causes a significant improvement of sexual function, including desire, arousal, and lubrification, compared to expectant management. Furthermore, it leads to a decrease in vaginal pH and an increase of the trophic status of vaginal epithelium.